Analisis Sedimentasi Lahan DAS Embung Uwai Kabupaten Kampar Menggunakan Metode Usle Berbasis Sistem Imformasi Geografis (SIG) - Muhammad Hadi Hasibuan; Bambang Sujatmoko; Mudjiatko Mudjiatko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Landuse change at Uwai watershed is causing increase on the amount of erotion. analisys of the potential of erotion on Uwai Watershed involves the sedimentation that occured on the watershed and also that enter the reservoir. The estimation method used to determine the magnitude of erotion occured is Universal Soil Loss Equation (USLE) by utilizing the Geographic Information System (GIS). The capacity of sediment transport is calculated based on equation by Verstraten. The result of the research showed that the watershed for Uwail is consisted of 44 subbasin, the highest sedimentation occured on subbasin 17 with the magnitude of 55,113.75 ton/year. Meanwhile the lowest sedimentation occcured on subbasin 33 with the magnitude of 123.03 ton/year. The erotion that enters the retention pool of Uwai which will be the sedimentation on the retention pool is 6199.9 ton/year. Hence the shallowing that will occur is 14,2 mm/year.Keywords: sedimentation, USLE, GIS,